65‐1: Invited Paper: Narrow Spectrum Deep Red Emitters for OLED Lighting and Display. Issue 1 (29th May 2019) - Margulies, Eric A.; Boudreault, Pierre-Luc T.; Adamovich, Vadim I.; Alleyne, Bert D.; Weaver, Michael S.; Brown, Julie J.
Abstract : We report narrow lineshape phosphorescent emitters enabling high luminous efficacy deep red emission for automotive lighting applications. As a result of the narrow 43nm FWHM and high efficiency, we achieve 16cd/A LE and 55, 000hr LT95 at 1, 000nits with a 640nm peak and 625nm dominant wavelength in a bottom emission device.